From Voluntary Compliance to Legal Obligation: Reformulating Indonesia's Zakat Law Through the Lens of Maqasid al-Shari'ah - Heri Siswan; Pagar Pagar; Nurul Huda Prasetiya (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
Law Number 23 of 2011 on Zakat Management recognizes zakat as a religious obligation for muzakki; however, the absence of legal consequences for non-compliance has resulted in a voluntary compliance model that limits the optimization of zakat collection in Indonesia. This study aims to analyze the normative gap between the obligatory nature of zakat and the existing legal framework and to formulate a maqasid al-shariah-based model for transforming zakat compliance from a voluntary practice into a legally enforceable obligation. This normative legal research employs statutory, conceptual, comparative, and Islamic jurisprudential approaches. The data are analyzed qualitatively through legal interpretation and doctrinal reasoning. The findings reveal that the primary weakness of Indonesia’s zakat regulatory framework lies not in the lack of normative recognition of zakat obligations but in the absence of an effective compliance and enforcement mechanism. This study proposes a Maqasid-based mandatory compliance model, which consists of three key elements: (1) legal recognition of zakat obligations, (2) institutional mechanisms for monitoring and ensuring compliance, and (3) proportionate administrative sanctions for economically capable muzakki who deliberately neglect their zakat obligations. From the perspective of maqasid al-shariah, this reformulation strengthens the protection of wealth (hifz al-mal), safeguards the rights of mustahik, and promotes distributive justice. Therefore, reforming Law Number 23 of 2011 is necessary to establish a balanced mandatory zakat system that enhances social welfare, improves the effectiveness of zakat governance, and maintains the principle of legal proportionality.